In-service materials support for safety critical applications - A case study of a high strength Ti-alloy using advanced experimental and modelling techniques - Rugg, D; Britton, T; Gong, J; Wilkinson, A; Bagot, P (2014)
This paper introduces motivations and suitability for using advanced characterisation techniques to study industrially relevant materials, such as titanium alloys for the aerospace industry. These advanced research tools each provide unique information in fundamental research, and by designing appropriate datum studies and modelling support they can be combined with powerful effect to tackle 'real world' engineering issues. We demonstrate the use of orientation-corrected nanoindentation, micro-cantilever bend testing and 3D atom probe tomography to investigate a high strength, dual phase engineering alloy (Ti-6Al-4V) with a surface gradient of interstitials. © 2014 Elsevier B.V.